Analisis Pengaruh Tenaga Kerja dan Pengangguran Terhadap Pertumbuhan Ekonomi di Indonesia - Sanusi Ghazali Pane; Windi Pramudya; Rica Cahya Amalya; Sheila Nur Aulia; Putri Nabila Pebriani (Economic Reviews Journal, 2024)
This study aims to evaluate the impact of labor and unemployment on economic growth in Indonesia, focusing on how these factors affect the dynamics of the national economy. The research method involves analyzing secondary data from economic and labor statistics reports, as well as reviewing literature to understand the relationship between these variables. The findings indicate that skilled and highly educated labor significantly contributes to increased productivity and efficiency in industries, thereby fostering more rapid and sustainable economic growth. Conversely, high unemployment rates negatively affect economic growth by reducing national income, consumer purchasing power, and consumption. Therefore, to stimulate more stable economic growth, it is crucial to reduce unemployment through effective job creation and enhancement of labor skills.